1989
DOI: 10.1007/bf01536255
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cholecystokinin and gallbladder responses to intraduodenal fat in gallstone patients

Abstract: Impaired gallbladder emptying is one of the various factors suggested to be involved in the pathogenesis of gallstones. The present study was undertaken to determine whether gallbladder emptying, endogenous cholecystokinin (CCK) secretion, or their interrelation is altered in patients with gallstones. After intraduodenal administration of 60 ml corn oil, plasma CCK concentration was measured by a sensitive and specific radioimmunoassay and gallbladder emptying by cholescintigraphy. Patients with gallstones (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Many studies have shown that gallbladder emptying is abnormal in patients with gallstones [20][21][22][23][24][25][26][27][28][29][30][31] . In addition, it has been observed that cystic duct flow resistance is increased before gallstone formation [32,33] .…”
Section: Wwwwjgnetcommentioning
confidence: 99%
“…Many studies have shown that gallbladder emptying is abnormal in patients with gallstones [20][21][22][23][24][25][26][27][28][29][30][31] . In addition, it has been observed that cystic duct flow resistance is increased before gallstone formation [32,33] .…”
Section: Wwwwjgnetcommentioning
confidence: 99%
“…So far, no convincing evidence has been reported of a role for CCK in gallstone disease. 10,14,19,20 The aim of the present study was to evaluate if there is any relationship between the dominating pathogenetic factors for gallstone development and body composition or fat distribution. Since obesity and, particularly, abdominal fat distribution is associated with disturbances in glucose and lipid metabolism, gallstone pathogenetic factors were also investigated in relation to these parameters in order to explain why some obese subjects develop gallstones and some do not.…”
Section: Introductionmentioning
confidence: 99%
“…Our study does not show differ ences in the maximum contraction, but rather in the sensitivity because it compares two groups of gallbladders: one with stones having an average cholesterol content of 94% (radiolucent gallstones) and the other with stones in which calcium is present (radi opaque gallstones) and whose cholesterol content is clearly greater than 3.5%, varying between 50 and 63%. Studies in the litera ture of in vivo gallbladder motility have focussed on a group of patients with stones that had a reduced sensitivity either to CCK or to fat meal (12,13]. Our in vitro study, while confirming altered sensitivity in vivo to neurohormonal stimuli, uses final concen trations of CCK-OP that are 1.000 times greater than plasma concentration.…”
Section: Discussionmentioning
confidence: 95%